Peran Majelis Ta’lim Berkat Sidin dalam Meningkatkan Pengetahuan Keagamaan dan Kehidupan Sosial di Masyarakat Sangatta Utara - Hasan Hasan; Eko Nursalim; Muhammad Fahriannor (PT. Pustaka Andil Lestari, 2026)
This study examines the role of Majelis Ta'lim Berkat Sidin in Sangatta Utara as a non-formal educational institution in improving community religious understanding and social life. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The findings show that Majelis Ta'lim Berkat Sidin strengthens congregants' religious knowledge through regular recitations discussing aqidah, sharia, and morals. Interactive learning methods, including discussions and question-and-answer sessions, also enhance participants' understanding of Islamic teachings. Beyond religious education, the majelis contributes to social solidarity through community activities such as fundraising and social services. Nevertheless, several challenges remain, particularly limited facilities and the need to improve teachers' competence. Overall, this study confirms the important role of Majelis Ta'lim as an agent of spiritual and social change that supports the development of harmonious communities grounded in Islamic values and encourages stronger religious practice, mutual care, and active participation within the wider local community.